Synthesis and antimicrobial activity of some novel derivatives of benzofuran: Part 2. The synthesis and antimicrobial activity of some novel 1-(1-benzofuran-2-yl)-2-mesitylethanone derivatives - Kirilmis, Cumhur; Ahmedzade, Misir; Servi, Sueleyman; Koca, Murat; Kizirgil, Ahmet; Kazaz, Cavit (Elsevier France-Editions Scientifiques Medicales Elsevier, 2008)
The reaction of salicylaldehyde with 1-chloro-3-mesitylacetone (2) and potassium carbonate was used to prepare 1-(1-benzofuran-2-yl)-2-mesitylethanone (4) for the starting reagent purposes. 1-(1-Benzofuran-2-yl)-2-mesitylethanoneoxime (5) was synthesized by the reaction of the compound (4) with hydroxylamine. New derivative of 1-(1-benzofuran-2-yl)-2-mesitylethanoneoxime (5) as 1-(1-benzofuran-2-yl)-2-mesitylethanonesemicarbazone (7) was obtained in very high yields. Alkyl substituted N-oxime ethers (8a-d) were obtained by the reaction compound 5 and various halogen contained compounds. The compounds 9a-d were synthesized by the reaction of the compound (5) and four different acyl chlorides. Some of the synthesized compounds were tested for antimicrobial activity against Staphylococcus aureus ATCC 6538, Escherichia coli ATCC 25922 and Candida albicans ATCC 10231. Among the synthesized. compounds (E)-1-(1-benzofuran-2-yl)-2-mesitylethanone-O-benzoyloxime (9b) was found the most active derivative against S. aureus ATCC 6538 and E. coli ATCC 25922. The other compounds exhibited moderate activity against the other test microorganisms. (c) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: antimicrobial activity; mesitylene; benzofuran; ketoxime